0268 Development of an Integrated Model of Sleep Deprivation in Adolescence. (27th May 2020) - Kwon, M; Park, E; Livingston, J A; Dean, G E; Suzanne, D S
Abstract: Introduction: Sleep deprivation is a consistently and widely concerning problem among adolescents. Although a few models have been proposed to explain the relationships and pathways through which factors influence sleep in adolescents, there are lack of theoretical models that apply both biological and behavioral factors that contribute to sleep deprivation across the trajectory of adolescent development. The current study proposes an integrated model that draws upon constructs from several influential theories with an aim to re-conceptualize factors associated with sleep deprivation as a chronic and cyclic problem that emerges from biological and behavioral changes in youth. Methods: The Two Process Model of Sleep Regulation, Spielman's 3p model, the theory of planned behavior, dual systems model, and sleep health framework are used to develop an integrated model of factors that lead to sleep deprivation in adolescents. Results: The resulting integrated model highlights the importance of adolescent's inherent nature of delayed sleep phase at pubertal onset ( two process model ); increased reward-seeking that precedes the structural maturation of their cognitive control and emotions ( dual systems model ); and their attitudes/perceptions towards sleep ( theory of planned behavior ), which is often geared toward not prioritizing sleep. Sleep health framework adequately frames the pattern of sleep-wakefulness in adolescents using a multidimensional approach of sleep. Moreover, the new model presents contextual factors ( Spielman's 3p model ) and the way that these constructs interact in order to maintain a vicious cycle of insufficient sleep which leads to chronic sleep deprivation. Conclusion: The current model portrays a wide-ranging view of mechanisms underlying sleep deprivation among adolescence by integrating both biological and behavioral aspects. The model is proposed to encourage researchers to explore these conceptual elements of biological and neurobiological changes, and behavioral problems in order to operationalize relevant measures to relate the concepts to sleep deprivation and subsequent health outcomes in adolescents. Support: None